Taxonomic novelties in Southern Brazilian Amaryllidaceae – II: Zephyranthes comunelloi a new species from Santa Catarina; and lectotypification of Zephyranthes mesochloa Herb. Ex Lindl. - Büneker, Henrique Mallmann; Bastian, Regis Eduardo (Balduinia, 2018)
Zephyranthes comunelloi, a new species of Amaryllidaceae (Amaryllidoideae, Hippeastreae) that occurs in grasslands of the central-western region of Santa Catarina (Brazil) is described and illustrated. Data are provided on their habitat, ecology and geographic distribution. The new species shows morphological affinity with Z. gratissima and Z. mesochloa; differing basically in the shape of the leaves, size and color of the tepals and position of the style. We have also proposed here a lectotype for Z. mesochloa.